Zero-Trust Security Investment and Firm Performance in AI-Enabled Internet of Things Environments - Wang, Chunhai (Asia Pacific Economic and Management Review, 2025)
This study examines how zero-trust security investment affects firm performance in AI-enabled Internet of Things (AI-IoT) environments and through which mechanisms and boundary conditions this influence occurs. Drawing on the resource-based view and dynamic capability perspectives, we conceptualize zero-trust security investment as a multidimensional capability bundle that integrates financial resources, technological deployment and organizational practices dedicated to implementing zero-trust principles in AI-IoT systems. Using survey data from 312 firms in AI-IoT–intensive industries in China and structural equation modeling, we find that zero-trust security investment is positively associated with firm performance. Digital resilience—defined as the firm’s ability to withstand, adapt to and recover from cyber-related disruptions—plays a partial mediating role in this relationship, indicating that security investments create value both by directly reducing expected losses and by enhancing the reliability and continuity of AI-IoT–enabled operations. Furthermore, environmental uncertainty positively moderates the effect of zero-trust security investment on firm performance, suggesting that the performance benefits of zero-trust security are stronger in volatile environments characterized by rapid technological change, evolving regulations and dynamic competitive behavior. These findings highlight zero-trust security as a strategic resource that underpins digital resilience and competitive advantage, and they offer practical guidance for managers and policymakers seeking to align cybersecurity investment with AI-IoT strategies and environmental conditions.